2016
DOI: 10.1097/mib.0000000000000930
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ostomy on Quality of Life and Functional Status of Crohnʼs Disease Patients

Abstract: Background The potential need for an ostomy is a main concern for patients with inflammatory bowel disease. We performed this study to evaluate the impact of a long term ostomy (≥ 6 months duration) on the functional status and specific patient-reported outcomes (PRO) in a population of patients with Crohn’s disease (CD). Methods We performed a cross-sectional analysis within the CCFA Partners cohort Study. Bivariate analyses and logistic regression models were used to investigate associations between ostomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 35 publications
3
49
3
Order By: Relevance
“…The depression degree in CD patients with ostomy showed statistically significant differences depending on marital status, monthly household income, length of sleep, and sleep disorder. This supports results from previous studies reporting marital and financial status as depression factors in CD patients . CD patients were almost younger than UC patients, and therefore, half the number of participants (32 patients, 50%) responded that they have a job and are in a phase of life wherein vigorous economic activity is required.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The depression degree in CD patients with ostomy showed statistically significant differences depending on marital status, monthly household income, length of sleep, and sleep disorder. This supports results from previous studies reporting marital and financial status as depression factors in CD patients . CD patients were almost younger than UC patients, and therefore, half the number of participants (32 patients, 50%) responded that they have a job and are in a phase of life wherein vigorous economic activity is required.…”
Section: Discussionsupporting
confidence: 89%
“…A Canadian study on the depression degree of IBD patients showed that poor health condition and poor nutrition were also significant influence factors of depresion . However, Abdalla and colleague observed significant associations between ostomy status and both fatigue amongst patients with clinically active disease but not for those in clinical remission to CD patients . Therefore, we suggest that further studies need to identify association between having an ostomy, fatigue, and depression in UC and CD patients with ostomy.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Among generally healthy populations, the mean T-score for pain interference, depression, anxiety, satisfaction with one’s social role, fatigue, and sleep disturbance is 50 with a standard deviation (SD) of 10. Based on prior studies evaluating the PROMIS measures in patients with IBD and other chronic conditions such as rheumatoid arthritis, 25,2932 a minimally important difference of 2 was assigned when analyzing PROMIS measures.…”
Section: Methodsmentioning
confidence: 99%